O Banco Mundial e a Educação Infantil no Brasil - MARQUEZ, Christine Garrido (2006)
This text is one of the several sub-projects that are in a development process integrated to the project Public Politics and Childhood Education in Goiás: history, conceptions, projects and pratices, linked to the research line Teacher Formation and Professionalism Process at Education Faculty in Goiás Federal University. We investigated the Brazilian scene that delineates around the public politics of Childhood Education subsidized by the World Bank. We carried through a critical reflection trying to understand the conceptual and political orientations of that Bank about the education, mainly, the childhood education and to identify projects that base their implementation in Brazil, since the 90 s years. Based on a dialectic-historical-social perspective, we developed a documental and bibliographic research. We started from an organizational vision from World Bank and its educational politics present in the Education Sector Documents (1971, 1974, 1980, 1995 and 2000) to, then, analyze the public politics elaborated, implemented and monitored for the children education from zero to six years old. We carried through a historical rescue of the financing public politics of the Brazilian and childhood educations, considering the extinction of the projects, programs and actions directed toward the first childhood, scattered by the social welfare and attendance areas, health, work and education. In the scope of the public education, we verified that the proposals of the bank became concrete constructed during the Brazilian educational history with the national consent and participation. The Childhood Education is taking place in the agenda of the World Bank, since the 90 s years, monitored by the economic vision that bases its global, particular, and mainly educational politics, enrolled in economic principles and in the public expenses reduction, incorporated as a component of the financed projects, through the informal alternative programs of low cost